Evaluation of Strategic Management and Growth Alternatives in Independent Auditing Firms Using Interval Type-2 Fuzzy ARAS Method - Durmuş, Cem Niyazi; Gorcun, Omer Faruk (Journal of Intelligent Decision Making and Information Science, 2025)
Independent audit firms (IAFs) need to base their strategic management and growth decisions on more logical and rational foundations due to the technological and digital transformation, which has been increasing pressure in the recent period, the intensification of competition in the industry, and the rapid and frequently changing structure of legal regulations. In this context, this study aims to evaluate and prioritize strategic management and growth decisions systematically and analytically by identifying the strategic decision problems faced by IAFs. In this direction, six strategic alternatives determined by a comprehensive field study were analyzed with the help of the Interval Type-2 Fuzzy ARAS (IT2F–ARAS) method, considering thirteen criteria determined based on expert opinions. IT2F–ARAS technique has been preferred as it can effectively include differences in interpretation in specialists’ judgments and ambiguities in the model. This procedure enables the integrated and flexible evaluation of quantitative and qualitative data in decision-making processes. When the results obtained by applying the proposed model are examined, it is seen that benefit-oriented criteria such as expanding the customer base, providing a competitive advantage, and increasing brand value are more decisive. It has been observed that cost-side criteria, such as initial investment cost and technological incompatibility, limit the applicability of some strategies. In addition, "digital transformation," "expanding the range of services," and "market diversification" have emerged as priority strategies for IAFs in the context of strategic management and growth decisions. The study aims to contribute to developing more consistent and sustainable growth policies by providing independent audit firms with a multi-criteria and fuzz-based decision support perspective in their strategic orientations.